The effects of mechanical instability on PDGF mediated inflammatory response at early stage of fracture healing under diabetic condition. (February 2023) - Zhang, Enhao; Miramini, Saeed; Patel, Minoo; Richardson, Martin; Ebeling, Peter; Zhang, Lihai
Highlights: Developed a numerical model for investigating the effects of mechanical instability on PDGF mediated inflammatory response at early stage of fracture healing under diabetic condition Mechanical instability could result in PDGF releasing at fracture site, and thereby promote local inflammatory response. Under diabetic condition, mechanical instability leads to a significant decrease of MSCs concentration in fracture callus. Mechanical instability can significantly affect the natural resolution of inflammation during the early stage of fracture healing. Abstract: Background and Objective: Mechanical stability plays an important role in fracture healing process. Excessive interfragmentary movement will continuously damage the tissue and newly formed capillaries at the fracture site, which leads to overproduction of platelet-derived growth factor (PDGF) that attracts more macrophages into fracture callus, ultimately persistent and enhanced inflammatory response happens. For diabetic condition, the impact of mechanical instability of fracture site on inflammatory response could be further compliciated and the relevant research in this field is relatively limited. Methods: Building on previous experimental studies, this study presents a numerical model consisting of a system of reactive-transport equations representing the transport as well as interactions of different cells and cytokines within the fracture callus. The model is initially validated by available experimental data, and then implemented to investigate the role of mechanical stability of fracture site in inflammatory response during early stage of healing. It is assumed that there is an increased release of PDGF due to the rupture of blood vessels resulting from mechanical instability, which leads to increased production of inflammatory cytokines ( i.e., TNF-α). The bone healing process under three different conditions were investigated, i.e., mechanically stable condition with normal inflammatory response (Control, Case 1), mechanically unstable condition with normal inflammatory response (Case 2) and mechanically unstable condition with diabetes (Case 3). Results: Mechanical instability can promote the macrophage infiltration and thus induce an enhanced and prolonged inflammatory response, which could impede the MSCs proliferation during the early fracture healing stage (e.g., compared with the control condition, the MSCs concentration in unstable fracture with normal inflammatory response can be reduced by 3.2% and 5.2% on day 2 and day 10 post-fracture, respectively). Under diabetic condition, the mechanical instability of fracture site could lead to a significant increase of TNF-α concentration in fracture callus (Case 3) in comparison to control (Case 1) ( e.g., three-fold increase in TNF-α concentration compared to control). In addition, the results show that the mechanical instability affects the cell differentiation and proliferation in fracture callus in a spatially dependent manner, e.g., for diabetic fracture patients, the mechanical instability could potentially decrease the concentration of MSCs, osteoblasts and chondrocytes by around 39%, 30% and 29% in cortical callus, respectively, in comparison to control. Conclusion: The mechanical instability together with diabetic condition can significantly affect the natural resolution of inflammation during early stage of healing by turning acute inflammation into chronic inflammation which is characterized by a continuously upregulated TNF-α pathway.